The effects of Watsu therapy on autonomic cardiovascular modulation and flexibility of children with cerebral palsy - ERTAN TUFEKCIOGLU (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2020)
Background: We aimed to compare and examine the effect of aquatic interventions, Watsu® vs Immersion, on the autonomic nervous system and the range of motion in children with cerebral palsy, due to common belief that use of Watsu is beneficial for the special needs. Material and methods: Twenty-three children (age 7.5±2.8) were randomized to receive Watsu® therapy and Immersion interventions in the cross-over, age-stratified study. Each therapy session lasted 30 minutes twice a week for a total of 10 weeks in two non-consecutive periods. Short-term heart rate variability parameters by using a Polar H7 heart rate sensor with a signal processing software and the passive range of motion by using a universal goniometer was measured at baseline and post-treatment. Results: Watsu® therapy significantly improved the heart rate variability parameter (pNN50, t = 2.312, p = 0.031) and lower flexibility (t = 6.012, p = 0.000) in comparison to immersion. Conclusions: In comparison to immersion, Watsu® therapy was shown to be safe and effective for the autonomic modulation and flexibility of children with cerebral palsy. Therefore, it is recommended as a complementary tool for physical therapy on land.